DETERMINAN KUALITAS AUDIT: PERAN AUDITOR SWITCHING, AUDIT TENURE, DAN AUDITOR GENDER (Studi Empiris pada Perusahaan Barang Konsumsi Primer yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024) - Hilda Karolina Duha; Herry Laksito (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of auditor switching, audit tenure, and auditor gender on audit quality in primary consumer goods companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Audit quality is proxied by the affiliation of Public Accounting Firms (PAFs) with the Big Four and non-Big Four. Profitability and firm size are included as control variables to obtain more reliable estimation results.The sample was selected using purposive sampling, resulting in 275 firm-year observations after data screening and outlier removal. The data were analyzed using binary logistic regression due to the dichotomous nature of the dependent variable. The findings indicate that auditor switching, audit tenure, and auditor gender do not have a statistically significant effect on audit quality.In contrast, the control variables—profitability and firm size—show a significant positive effect on audit quality. This suggests that companies with higher profitability and larger asset bases are more likely to engage Big Four audit firms. Overall, firm characteristics play a more dominant role in determining audit quality than auditor-related characteristics within the context of this study.